An effective elastic thickness map of Australia from wavelet transforms of gravity and topography using Forsyth's method - Swain, Christopher; Kirby, Jonathan (American Geophysical Union, 2006)
We have developed a wavelet version of Forsyth's coherence method for estimating the effective elasticthickness (T e) of the lithosphere from gravity and topography. We have previously shown that the 'fan' wavelet is particularly well suited to making localised coherence estimates and here we progress the method by showing how the coherence can be modelled by using the wavelet transforms of gravity and topography to infer the initial loads that flex the plate. The effectiveness of the method is demonstrated on synthetic data from a model having a rectangular area of large T e embedded in a uniform low T e surrounding, and a load ratio that increases with wave number. The results for the Australia region show a 'core' of high T e under north and central Australia, with much lower values to the east and also, unexpectedly, under the western parts of the Yilgarn and Pilbara cratons.